Surface Reconstruction and Decahedral Structure of Bimetallic Nanoparticles - Rodríguez López J. L. (2004)
We report on energetic surface reconstruction phenomena observed on bimetallic nanoparticle systems of AuPd and AuCu, similar to a resolidification effect observed during the cooling process in lead clusters. These binary alloy nanoparticles show the fivefold edges truncated, resulting in { 100 } facets on decahedral structures, an effect largely envisioned and reported theoretically, with no experimental evidence so far. We demonstrate experimentally as well as by computational simulations that this new eutectic structure is favored in such nanoalloy systems.